2019
DOI: 10.1128/jvi.01885-18
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Arrest in G 2 /M Phase Enhances Replication of Interferon-Sensitive Cytoplasmic RNA Viruses via Inhibition of Antiviral Gene Expression

Abstract: Vesicular stomatitis virus (VSV) (a rhabdovirus) and its variant VSV-ΔM51 are widely used model systems to study mechanisms of virus-host interactions. Here, we investigated how the cell cycle affects replication of VSV and VSV-ΔM51. We show that G2/M cell cycle arrest strongly enhances the replication of VSV-ΔM51 (but not of wild-type VSV) and Sendai virus (a paramyxovirus) via inhibition of antiviral gene expression, likely due to mitotic inhibition of transcription, a global repression of cellular transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 76 publications
(88 reference statements)
0
39
0
Order By: Relevance
“…Control of cell cycle dynamics is a likely mechanism by which nutrient status affects proliferation. Cells exit the cell cycle for a variety of reasons, including G0 cell cycle exit for differentiation, or irreversible G2 arrest in response to DNA damage (Barnum and O'Connell, 2014;DiPaola, 2002;Duursma and Cimprich, 2010) or viral infection (Bressy et al, 2019;Davy and Doorbar, 2007). Dividing cells typically pause for some period in G0, pending signals that regulate progression into G1 and subsequent cell division or terminal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Control of cell cycle dynamics is a likely mechanism by which nutrient status affects proliferation. Cells exit the cell cycle for a variety of reasons, including G0 cell cycle exit for differentiation, or irreversible G2 arrest in response to DNA damage (Barnum and O'Connell, 2014;DiPaola, 2002;Duursma and Cimprich, 2010) or viral infection (Bressy et al, 2019;Davy and Doorbar, 2007). Dividing cells typically pause for some period in G0, pending signals that regulate progression into G1 and subsequent cell division or terminal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The cell lines SUIT-2 and MIA PaCa-2 were chosen because of their differential permissiveness to VSV and other differences. SUIT-2 cells are more resistant to VSV infection in part because of residual type I IFN responses, yet permissive enough to support sufficient viral replication to produce enough viral progeny for continued viral passaging, while MIA PaCa-2 cells are very permissive to VSV infection in part due to their inactive type I IFN signaling (37,41,66). Also, we showed that SUIT-2 cells showed lower levels of VSV attachment, compared to MIA PaCa-2 cells (44).…”
Section: Resultsmentioning
confidence: 69%
“…Our previous analysis of permissive and resistant PDAC cell lines identified at least 2 mechanisms responsible for resistance of SUIT-2 cells to VSV. First, SUIT-2 cells are able to induce a functional type I IFN response to VSV (37,41,66). Second, we observed that, compared to MIA PaCa-2 and some other tested PDAC cell lines, VSV attaches less efficiently to SUIT-2 cells (44).…”
Section: Vsv-p53-cc (Suit-2) G: M184imentioning
confidence: 77%
See 1 more Smart Citation
“…The G 2 /M transition is the last checkpoint in the cell cycle, and passing this checkpoint allows the cell to divide into two daughter cells. Studies have shown that viruses induce arrest at the G 2 /M transition via a variety of different methods (40)(41)(42)(43). The HIV Vpr protein induces host cell arrest at the G 2 /M transition by activating ATR to interact with Cdc25C, thereby inhibiting its phosphatase activity (44,45).…”
Section: Discussionmentioning
confidence: 99%